Strategies For Implementing Character Education In The Post-Covid-19 Pandemic Period Through The Example Of Teachers And Dormitory Supervisors (Case Study At Smp Nuraida Islamic Boarding School) - Desi Metri Kusumaningtyas; Nandang Hidayat; Herfina Herfina (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Some time ago, when the world was hit by the Covid-19 pandemic, many life deposits experienced shocks, including the education sector. It is undeniable that in any part of the world, many students experience learning loss. And many studies have also been conducted related to the condition of learning loss. Where all school activity programs seem to be unrequited, teachers are unable to maximally educate the character of their students. Very different from conditions before the COVID-19 pandemic. This condition was also felt by a boarding school in the North Bogor sub-district of Bogor City. There are so many students who until the post-pandemic period still experience character deviations. This encourages schools to be responsive so that this character change crisis can be handled immediately. This paper will try to analyze the factors that cause changes in the character of students in this school in the post-pandemic period and find the right strategy to overcome them. The research conducted at SMP Nuraida Islamic Boarding School used qualitative methods of data collection techniques through observation, interviews, and document studies. This research is expected to be able to find new strategies to overcome the conditions of character change that occur in the post-COVID-19 pandemic.  Keywords: character change; Strategy; Boarding School.